PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA MELALUI MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA KOTAK KEHIDUPAN PADA TEMA 6 CITA-CITAKU - Syarifa Rahma Amalia; Fina Fakhriyah; Sekar Dwi Ardianti (WASIS : Jurnal Ilmiah Pendidikan, 2020)
This research described implementation of Problem Based Learning to improve teacher’s teaching skill, the students’ learning activities, and critical thinking ability of the students.This classroom action research was conducted for fourth graders of SD 1 Barongan Kudus. consisting of 41 students. It lasted in two cycles. The independent variables were Problem Based Learning model and life box. The dependent variables were critical thinking ability. Data collections in this research consist are test, observation, interview, and documentation. The data analysis were quantitative and qualitative.The result showed improvement. Teacher's skill improved in cycle I, from 78.7 into 89.1 in cycle II. The students’ learning activities improved from cycle I, 78.8 into cycle II, 88.6. Critical thinking ability of the students from cycle I, 73.2 improved into 86.8 in cycle II.It is concluded that critical thinking ability of the students could be improved through Problem based Learning model with life box media in SD 1 Barongan Kudus.